2022
DOI: 10.3390/ijerph19074247
|View full text |Cite
|
Sign up to set email alerts
|

Green Walkability and Physical Activity in UK Biobank: A Cross-Sectional Analysis of Adults in Greater London

Abstract: Urban greenspace provides opportunities for outdoor exercise and may increase physical activity, with accompanying health benefits. Areas suitable for walking (walkability) are also associated with increased physical activity, but interactions with greenspace are poorly understood. We investigated associations of walkability and green walkability with physical activity in an urban adult cohort. We used cross-sectional data from Greater London UK Biobank participants (n = 57,726) and assessed walkability along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Participants living in rural areas reported spending more time outdoors than those living in urban areas, in both of our surveys. Spending time outdoors in a natural environment can improve health and wellbeing [ 33 ], and those living in cities spend more time doing physical activities if they live near urban green spaces [ 34 ]. Additionally, a longitudinal study conducted during COVID-19 stay-at-home orders (n = 20,012) found that spending time outdoors in nature and undertaking physical activity both significantly reduced depression and anxiety scores.…”
Section: Discussionmentioning
confidence: 99%
“…Participants living in rural areas reported spending more time outdoors than those living in urban areas, in both of our surveys. Spending time outdoors in a natural environment can improve health and wellbeing [ 33 ], and those living in cities spend more time doing physical activities if they live near urban green spaces [ 34 ]. Additionally, a longitudinal study conducted during COVID-19 stay-at-home orders (n = 20,012) found that spending time outdoors in nature and undertaking physical activity both significantly reduced depression and anxiety scores.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of documents (Figure 16), the node with the greatest size, and thus the most popular among recent walkability indicator studies, is Duncan et al's work [61], which validates the Walk Score ® [62] for estimating neighborhood walkability in 4 USA cities. [26][27][28][63][64][65][66]. Another topic of general interest for Public Health is people's physical health, manifested through obesity, overweight and frailty, and generally calculated using the Body Mass Index (BMI) or Waist Circumference (WC) [67][68][69][70][71].…”
Section: Citation Analysismentioning
confidence: 99%
“…Fewer works developed and implemented their own indicators. The new indicators that were identified during the research are: the Dutch Walkability Index [120] and the Japanese Walkability Index [112], both falling under the Transportation category; the Walkability Index for London [63], used to measure the relationship between green spaces and physical activity; and the School Walkability Index [121] applied to understand walkability associations with active commuting to school (ACS).…”
Section: Rq2: What Are the Most Used Walkability Indicators In Recent...mentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 14 Some measures have been added into studies to account for these complexities, such as the incorporation of vegetation data to assess “green walkability” and integration of perceived walkability measures that additionally draw on subjective assessments of traffic and crime safety levels. 15 , 16 An ongoing challenge of walkability exposure assessment is the lack of data that enable parameterization of each component of walkability, with the spatial and temporal range to support prospective study designs. In the context of cancer epidemiology, assessing walkability exposure over etiologically relevant time windows (e.g., decades) requires historical data sets.…”
mentioning
confidence: 99%